2011
DOI: 10.1080/09585192.2011.561238
|View full text |Cite
|
Sign up to set email alerts
|

Host country language ability and expatriate adjustment: the moderating effect of language difficulty

Abstract: Research has shown that expatriates' host country language ability is positively associated with their adjustment. But does the advantage of expatriates' language ability depend on the difficulty of the host language? To examine this issue, data were collected from expatriates in two European countries, one with an easy, relatively simple language and the other one with a difficult, highly complex language. Consistent with Goal Setting Theory, results indicated a relative advantage of expatriates' language abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 73 publications
5
92
0
1
Order By: Relevance
“…The meta-analysis of Bhaskar-Shrinivas et al (2005) found that language competence is related to both work and interaction adjustment. As a consequence of the relationship between language skills and CCA, language proficiency has been considered a positive predictor of the international assignee's effectiveness (Caligiuri et al, 2009;Lauring, 2008;Mol et al, 2005, Selmer & Lauring, 2015. Thus, there is substantial evidence that fluency in the local language is an important factor for expatriate adjustment since language seems to be an essential instrument through which expatriates develop their understanding of the new culture (Selmer, 2006b;Selmer & Lauring, 2015).…”
Section: Research On Expatriate Effectivenessmentioning
confidence: 99%
“…The meta-analysis of Bhaskar-Shrinivas et al (2005) found that language competence is related to both work and interaction adjustment. As a consequence of the relationship between language skills and CCA, language proficiency has been considered a positive predictor of the international assignee's effectiveness (Caligiuri et al, 2009;Lauring, 2008;Mol et al, 2005, Selmer & Lauring, 2015. Thus, there is substantial evidence that fluency in the local language is an important factor for expatriate adjustment since language seems to be an essential instrument through which expatriates develop their understanding of the new culture (Selmer, 2006b;Selmer & Lauring, 2015).…”
Section: Research On Expatriate Effectivenessmentioning
confidence: 99%
“…From an economic perspective, Gary Becker's (1992) notion of the importance of human capital is apparent in the large body of research that consistently indicates that one's language abilities (when one is operating in a 'host'/non-native environment, i.e., as an immigrant) condition access to information and labor market opportunities. In a multinational firm setting, language skills influence the cross-cultural adjustment of expatriates (Selmer and Lauring 2015;Zhang and Peltokorpi 2015) and individual employees' career mobility (Itani et al 2015;Latukha et al 2016). Moreover, multilingual employees find it easier to create social capital (Barner-Rasmussen et al 2014), enabling them to function as boundary spanners, language nodes, and information gatekeepers (Heikkilä and Smale 2011;Peltokorpi and Vaara 2012).…”
Section: Individual Level Perspectivesmentioning
confidence: 99%
“…This research has increasingly provided empirical evidence regarding key factors in the adjustment process, such as host country language ability and time spent in the host country (Bhaskar-Shrinivas, Harrison, Shaffer, & Luk, 2005;Black et al, 1991;Selmer & Lauring, 2011). Nevertheless, few statements about expatriates versus local nationals are based on empirical evidence (Boyacigiller, 1990), and some results indicate that expatriate managers are no more loyal to the company than are host country nationals (Banai & Reisel, 1993).…”
Section: Framework Of Subsidiary Ceo Perceptionsmentioning
confidence: 99%
“…The expatriate adjustment literature has demonstrated that, although expatriates are socialized in that they adjust to the host country's cultural norms, the degree of adjustment may depend on the length of assignment in the host country (Bhaskar-Shrinivas et al, 2005;Waxin, 2004). In general, sociocultural adjustment has been associated with variables that facilitate cultural learning and the acquisition of language and social skills in the host culture (Selmer, 2006;Selmer & Lauring, 2011).…”
Section: Framework Of Subsidiary Ceo Perceptionsmentioning
confidence: 99%